Calculation of Voltage-Current Characteristics of Field-Effect Transistors in Integrated Circuits by Analytical Methods - V. A. Bondarev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2006)
Analytical solutions and formulae for calculating current-voltage static characteristics of MOS transistors are presented. Calculations are based on verifications of a charge conservation principle which makes it possible to determine the expected parameters of new devices at different process conditions. Computer programs also take into account boundary conditions that take place at the p-n-junction in a drain region and greatly influence on operational modes of transistors. Results have also been used for the analysis of various physical processes concerned with a charge transfer. This cannot be usually carried out by means of existing numerical schemes. Algorithms for determination of an electron mobility and quasi-Fermi levels are developed. Programs also involve analytical formulae obtained earlier by the author for calculations of impurity distribution curves.